PERBAIKAN CARA ANGKAT-ANGKUT MATERIAL BANGUNAN MENGURANGI AKTIVITAS LISTRIK OTOT ERECTOR SPINAE DAN KELUHAN MUSKULOSKELETAL TUKANG BANGUNAN - Muliarta, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2015)
The development of the property sector bring consequency increasing number of skillfull labour who work in this sector. They work as a conventional management. One of the activity is lifting and carrying building material. Less ergonomic lifting and carrying due to  increasing  in the electrical activity of erector spinae muscle and musculoskeletal complaints among skillfull labours.The aim of the study was to determine that the improvement of lifting and carrying building material may reduce erector spinae muscle electrical activity and musculoskeletal complaints among skillfull labours. This study was using the experimental design extended by treatment by subject design. Samples were taken by purposive sampling, involving 11 males skillfull labour with a mean age of 38.5 ± 7.4 years. The results showed that the average electrical activity of erector spinae muscles in 1stPeriod 36.95 ± 3.85 % and in 1ndperiod 4.10 ± 1.10 % . Statistically, there was a decrease in the electrical activity of erector spinae muscles about 32.85 or 88.90 % with a 95 % CI 30.22 to 35.48 (p=0.000). The mean score of musculoskeletal complaints in 1stPeriod 50.36 ± 2.54 and in 2ndperiod 38.82 ± 4.36. Statistically, there was a decrease in musculoskeletal complaints score 11.54 or 22.92% with a 95 % CI 7.66 to 15.43 (p=0.000).From this research can be concluded that the improvement of lifting-carrying building material  reduce  erector spinae muscle electrical activity 88.90% and musculoskeletal complaints 22.92%  among skillfull labours
Keywords: electrical activity of muscles, erector spinae muscles, building material, skillfull labour, musculoskeletal complaints